Extrinsic Influence Factors in Software Reliability: A Study of 200,000 Windows Machines - Bird, Christian; Ranganath, Venkatesh-Prasad; Zimmermann, Tom; Nagappan, Nachi; Zeller, Andreas (Proceedings of the 36th International Conference on Software Engineering (ICSE 2014), 2014)
Reliability of software depends not only on intrinsic factors such as its code properties, but also on extrinsic factors—that is, the properties of the environment it operates in. In an empirical study of more than 200,000 Windows users, we found that the reliability of individual applications is related to whether and which other applications are installed: While games and file-sharing applications tend to decrease the reliability of other applications, security applications tend to increase it. Furthermore, application reliability is related to the usage profiles of these applications; generally, the more an application is used, the more likely it is to have negative impact on reliability of others. As a consequence, software testers must be careful to investigate and control these factors.